Catalytic and Atom-Economic Intermolecular Amidoselenenylation of Alkenes - Tang, E.; Wang, Weilin; Zhao, Yinjiao; Zhang, Meng; Dai, Xin (Organic letters, 2016)
A method for the simple, efficient, and atom-economic amidoselenenylation of simple alkenes under mild conditions using TiCl4 as a catalyst and N-(phenylseleno)phthalimide as both a nitrogen and selenium source was developed. A broad range of olefins can be applied to afford vicinal amidoselenides in good yield and with high regioselectivity and diastereoselectivity.